THE STOMACH - Murodullayev Khumoyun Izzatillo o’g’li; Pardayev Dilmurod Shermuhammadovich; Musurmonova Marjona Samandar qizi; Khasanov Farrukhjon Sherali o‘g‘li (TADQIQOTLAR, 2025)
Abstract: Role of the digestive tract in the digestive system. Anatomical, physiological and histological structure of the stomach. Relationship between them and the extent to which they are bounded by the body. Information about infectious and non-infectious diseases of the stomach at present. In what countries are the most common stomach diseases in the world? How many people suffer from such illnesses and how many percent of annual deaths. Measures to combat the diseases of the digestive system in the world.